PERGESERAN TRADISI RARAK OGUANG DALAM UPACARA PERKAWINAN MASYARAKAT DESA TANJUNG SIMANDOLAK KECEMATAN BENAI KABUPATEN KUANTAN SINGINGI - Fela widya wansriani; Ahmad Eddison; Haryono Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research is based on the shift of the rarak oguang tradition at the wedding ceremony in the village of Simandolak, Benai sub-district, Kuansing district. to accompany the bride by means of the local language bararak simandolak, and rarak oguang at this time it is rarely used in wedding parties. Is this oguang rarak no longer there or the person who plays it does not exist and it could also be because of technological advances over the times. So that researchers are interested in researching the challenge of the Shifting of Rarak Oguang Tradition in the Marriage Ceremony of the Simandolak Village Community, Benai District, Kuansing Regency. In managing the data, the researcher used a qualitative method, the number of research informants was 5 people who were taken from the rarak oguang workers and also community leaders in the Simandolak village. The data collection technique used by researchers is to use the method of interviewing, observation, documentation, the researcher formulates the problem, namely How is the condition of the Rarak Oguang Tradition in the Marriage Ceremony of the Simandolak Village community, Benai District, Kuantan Singingi Regency. The results of the research are: Rarak oguang is rarely used because of the existence of a new and more modern instrument or music than the rarak oguang. The lack of musical instruments from the rarak oguang tradition is one of the causes of this shift from the rarak oguang tradition. In the past, there was no tribe that did not have this traditional musical instrument because if the tribe did not have a gong, then the whole tribe would be ashamed because the gong was considered a spirit in the tribe, in modern times today the people of Kuantan Singingi, especially Benai District, where the people who were married were enough to promote a tradition that The so-called rarak tradition or traditional ceremony has now shifted to 2 days, the first day is enlivened by a traditional ceremony or rarak tradition and the second day with a general procession.Key Words: Shift, Tradition, Rarak Oguang